Changes in cardiovascular-health blood biomarkers in response to exercise intervention among older adults with cognitive frailty: A scoping review - Ibrahim, Azianah; Mat Ludin, Arimi Fitri; Singh, Devinder Kaur Ajit; Rajab, Nor Fadilah; Shahar, Suzana (Frontiers in Physiology, 2023)
Introduction: Cardiovascular health contributes significantly to the incidence of cognitive impairment. Prior to conducting exercise-related intervention, it is crucial to explore cardiovascular health blood parameters that have been commonly used as guidance for the purpose of monitoring. Information on the effectiveness of exercise on cardiovascular-related biomarkers is lacking, especially among older adults with cognitive frailty. Therefore, we aimed to review existing evidence on cardiovascular-related blood parameters and their changes following exercise intervention among older adults with cognitive frailty. Methods: A systematic search was conducted on PubMed, Cochrane, and Scopus databases. Related studies involving only human and full text in either English or Malay language were selected. Types of impairment were limited to cognitive impairment, frailty, and cognitive frailty. Studies were restricted to randomized controlled trial and clinical trial design studies. For charting purposes, all variables were extracted and tabulated. Trends in types of parameters studied were explored. Results: A total of 607 articles were screened, and the final 16 were included in this review. Four cardiovascular-related blood parameter categories were extracted: inflammatory, glucose homeostasis, lipid profile, and hemostatic biomarkers. The common parameters monitored were IGF-1 and HbA1c, glucose, and insulin sensitivity in some studies. Out of the nine studies on inflammatory biomarkers, exercise interventions showed a reduction in pro-inflammatory markers, namely, IL-6, TNF-α, IL-15, leptin, and C-reactive protein and an increase in anti-inflammatory markers, namely, IFN-γ and IL-10. Similarly, in all eight studies, glucose homeostasis-related biomarkers had improved with exercise intervention. The lipid profile was tested in five studies, with four studies showing improvements with exercise intervention via a decrease in total cholesterol, triglycerides, and low-density lipoprotein and an increase in high-density lipoprotein. A decrease in pro-inflammatory biomarkers and an increase in anti-inflammatory biomarkers were demonstrated with multicomponent exercise, including aerobic exercise in six studies and aerobic exercise on its own in the remaining two studies. Meanwhile, four out of six studies that yielded improvements in glucose homeostasis biomarkers involved only aerobic exercise and the remaining two studies involved multicomponent with aerobic exercise. Conclusion: The most consistent blood parameters studied were glucose homeostasis and inflammatory biomarkers. These parameters have been shown to improve with multicomponent exercise programs, particularly with the inclusion of aerobic exercise.